УПРОСТИТЕ ВЫРАЖЕНИЕ! АЛГЕБРА 10 КЛАСС

+535 голосов
2.9m просмотров

УПРОСТИТЕ ВЫРАЖЕНИЕ! АЛГЕБРА 10 КЛАСС


Алгебра | 2.9m просмотров
Дан 1 ответ
+195 голосов

{8}^{ \frac{1}{6} } ( {8}^{ \frac{1}{6}} - 4) - {( {8}^{ \frac{1}{6} } - 2)}^{2} = ( { {2}^{3} })^{ \frac{1}{6} } (( { {2}^{3} })^{ \frac{1}{6} }- 4) - {(( { {2}^{3} })^{ \frac{1}{6} } - 2)}^{2} = {2}^{ \frac{1}{2} } ( {2}^{ \frac{1}{2} } - 4) - {( {2}^{ \frac{1}{2} } - 2) }^{2} = {2}^{ \frac{1}{2} } \times {2}^{ \frac{1}{2} } - 4 \times {2}^{ \frac{1}{2} } - (2 - {2}^{ \frac{5}{2} } + 4) = \sqrt{2} \times \sqrt{2} - 4 \times \sqrt{2} - (6 - {2}^{ \frac{5}{2} } ) = 2 - 4 \sqrt{2} - (6 - \sqrt{ {2}^{5} } ) = 2 - 4 \sqrt{2} - (6 - 4 \sqrt{2} ) = 2 - 4 \sqrt{2} - 6 + 4 \sqrt{2} = - 4

ответ: -4

(1.4k баллов)